An approach to the development of connections between fibre reinforced polymer bridge decks. (June 2016) - Mara, Valbona; Kliger, Robert
Highlights: A systematic approach to the development of the connections between the FRP deck panels is presented. Collaborative working can deliver innovative technology solution. Design for assembly and manufacture (DFMA) concept is efficient in the development of connections in construction. Abstract: The use of fibre reinforced polymer (FRP) bridge decks has attracted increasing interest as a competitive alternative to traditional decking solutions. Even though the use of FRP decks started in the early 1990s, the uptake of these decks has been slow in bridge construction and there remains a need for research in diverse technical areas to promote the widespread use of these decks. One such area is the detailing and design of deck panel level connections which enable rapid on-site assembly. The development of connections in FRP decks is a somewhat complex process, which should take account of not only the structural performance and durability of the joint but also the ease of application and the tolerances this necessitates. It should therefore be regarded as a process in which the bridge owner, the designer, the manufacturer and the contractor are all involved. This process has been applied in the development of a novel joint configuration for panel level connections presented in this paper. The collaboration between the bridge owner, designer, manufacturer and contractor led to the development of a connection concept, in which expectations originating from the views of all parties were included. In this way, a concept focusing on meeting the requirements of all bodies was designed.